RESPON POLITIK HUKUM ISLAM TERHADAP TANTANGAN GLOBALISASI DALAM MENENTUKAN ARAH KEBIJAKAN PENDIDIKAN ISLAM - Ichwan, Ichwan (AL-IBNOR, 2026)
Islamic education in Indonesia faces significant challenges, including public skepticism toward Islamic institutions, weak vision and mission, overloaded curricula, and low competitiveness of graduates in both national and global contexts. Globalization has intensified these challenges by transforming learning through information and communication technologies, making education more interactive and accessible, yet also introducing negative impacts such as commercialization and exposure to uncontrolled information. To remain relevant, Islamic educational institutions must revise their vision and mission, adapt to rapid environmental changes, and balance religious and general knowledge in their curricula. Institutions must produce graduates equipped with moral, intellectual, and practical skills to compete effectively in a globalized workforce. Addressing these challenges requires a holistic and strategic approach that emphasizes quality organizational culture, visionary leadership, and responsive management. By fostering ethical values, accountability, and innovation, Islamic educational institutions can develop graduates capable of thriving in a competitive global environment while maintaining religious integrity. This integrated approach ensures that Islamic education contributes meaningfully to national development, prepares students for global challenges, and strengthens the sustainability and relevance of Islamic educational institutions in Indonesia’s evolving socio-economic and technological landscape.